Social media marketing dynamics in the beauty industry: Analyzing the synergistic effects of content marketing and online customer reviews on Hanasui Product purchase intentions through Tiktok - Juita L D Bessie; Diana A N Obe (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study investigates the influence of content marketing and online customer reviews on consumers’ purchase intention toward Hanasui beauty products among followers of the TikTok account @officialhanasui. Adopting a quantitative approach, data were collected from 100 respondents selected through purposive sampling using a structured questionnaire and analyzed using multiple linear regression with SPSS 26. The findings reveal that both content marketing and online customer reviews have positive and significant effects on purchase intention, both individually and jointly. The model demonstrates strong explanatory power, indicating that these two variables account for a substantial proportion of the variation in consumers’ purchase intention. The results suggest that engaging content and credible customer reviews play complementary roles in strengthening consumer confidence and encouraging purchase decisions on social commerce platforms. This study contributes to the growing literature on social media marketing by highlighting the importance of integrating content-driven strategies with user-generated reviews to stimulate consumer purchase intention in the digital beauty market. Future research is encouraged to incorporate additional factors, such as influencer credibility, online customer ratings, and viral marketing, to provide a more comprehensive understanding of consumer behavior on TikTok. Keywords: Content Marketing; Online Customer Review; Purchase Intention